Contribution of Ebullition to Methane and Carbon Dioxide Emission from Water between Plant Rows in a Tropical Rice Paddy Field. (29th December 2015) - Komiya, Shujiro; Noborio, Kosuke; Katano, Kentaro; Pakoktom, Tiwa; Siangliw, Meechai; Toojinda, Theerayut
Abstract : Although bubble ebullition through water in rice paddy fields dominates direct methane (CH4 ) emissions from paddy soil to the atmosphere in tropical regions, the temporal changes and regulating factors of this ebullition are poorly understood. Bubbles in a submerged paddy soil also contain high concentrations of carbon dioxide (CO2 ), implying that CO2 ebullition may occur in addition to CH4 ebullition. We investigated the dynamics of CH4 and CO2 ebullition in tropical rice paddy fields using an automated closed chamber installed between rice plants. Abrupt increases in CH4 concentrations occurred by bubble ebullition. The CO2 concentration in the chamber air suddenly increased at the same time, which indicated that CO2 ebullition was also occurring. The CH4 and CO2 emissions by bubble ebullition were correlated with falling atmospheric pressure and increasing soil surface temperature. The relative contribution of CH4 and CO2 ebullitions to the daily total emissions was 95–97% and 13–35%, respectively.